Latent tuberculosis infection and screening method among close contacts in schools in Xuhui District，Shanghai from 2020 to 2022 - ZHANG Sainan; YANG Meixia; CAI Xiaofeng; XU Xiang; ZHANG Yi (Shanghai yufang yixue, 2023)
ObjectiveTo investigate the latent tuberculosis infection （LTBI） of close contacts in schools of Xuhui District， and to explore the tuberculin skin test （TST）- interferon-γ release assay （IGRA） two-step method in order to discover the screening strategy of tuberculosis in Xuhui District.MethodsClose contacts of tuberculosis in schools of Xuhui District from 2020 to 2022 were selected as research subjects. Screening was conducted using symptom questionnaire， TST， chest X-rays， IGRA， and the information including the etiological results and grade of the index cases， as well as gender， age， and relationship with the index cases of the research subjects were collected.ResultsTotally 615 close contacts of 32 tuberculosis cases occurred in the schools were finally included. Of the 609 close contacts who completed tuberculosis infection screening and underwent TST testing， 153 TST（+） individuals underwent IGRA testing. The final LTBI rate was 4.6%， and the pulmonary tuberculosis detection rate was 163 per 100 000. The relationship with the index cases was an influencing factor for LTBI. The IGRA positivity rate was higher among close contacts with TST ≥15 mm than among those with 10 mm≤ TST <15 mm （χ2=14.41， P<0.05）.ConclusionThe latent tuberculosis infection among close contacts of school tuberculosis cases in Xuhui District remains serious. TST-IGRA two-step method can assist in the accurate diagnosis of LTBI and pulmonary tuberculosis cases.